FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN TERHADAP PELAYANAN DI BANDUNG GIRI GAHANA GOLF & RESORT : Studi Ke Arah Pengembangan Program Peningkatan Pelayanan diBandung Giri Gahana Tahun 2009 - Herman Yusiwa, - (2010)
Many tourism industry is trying to focus on high customer satisfaction, due to low consumer satisfaction, will be easy to change his mind if a better offer. High satisfaction will create an emotional attachment to the service or a specific tourist product. Thus, the result is high customer loyalty. The purpose is to provide services to the customers satisfaction. Consumers have an expectation of a product, whether goods or services to be purchased. If the product is in accordance with the consumer expectations, consumers will feel happy because their needs are met. Conversely if the consumer needs are not met then the consumer is going to complain or switch to other producers with similar products. The population of this study is consumers who make a visit to Bandung Giri Gahana Golf & Resort. The method used in this research is descriptive. The data used are primary data and secondary data through surveys, literature study and observation Quality of service Bandung Giri Gahana Golf & Resort is still low and need repairs and improvements in every dimension of service quality. Based on the results of the calculation factor tangibles, Empathy & responsiveness is still at a low category, so these factors need improvement in order to improve the quality of service in Bandung Giri Gahana and one way is by training and education.